Biosynthesis of Au, Ag and bimetallic Au-Ag nanoparticles using aqueous leaf extract of cosmos caudatus - Mohamad, Rapidah (2013)
There is great interest in synthesizing metal nanoparticles due to their remarkable application in medicinal, catalysis and electronic. Single step biosynthetic approaches utilising plant extracts have emerged as a simple, ecofriendly and viable alternative to chemical synthetic procedures and physical methods. In the present study, we have synthesized mono- and bimetallic gold and silver nanoparticles by reduction of Au3+ and Ag+ ions using aqueous leaf extract of Cosmos caudatus (ulam raja). The formation of the Au and Ag nanoparticles was monitored using UV-Vis spectroscopy and was visually confirmed by colour change from yellowish to violet and from colourless to dark brown, respectively. The surface plasmon resonance (SPR) band appeared at 536 nm and 439 nm for Au and Ag, respectively. Meanwhile, competitive simultaneous reduction of Au3+ and Ag+ ions present in same solution led to the production of bimetallic Au-Ag in which the SPR band appeared at 533 nm. The nanoparticles were also characterised by using TEM, FESEM-EDX, XRD and FTIR analyses. FESEM micrographic images show the spherical shape for both gold and silver nanoparticles with average particle size 22.79 ± 6.81 and 21.49 ± 7.43, respectively. TEM images of the bimetallic Au-Ag nanoparticles showed the spherical shape of nanoparticles with average particles size of 13.98 ± 6.21 nm. Profile EDX spectra show the signals for both Au and Ag in the sample of AuNPs and AgNPs, respectively. Both signals appear for bimetallic sample, indicating that the bimetallic Au-Ag was in alloy form. X-ray diffraction (XRD) analysis revealed that the mono- and bimetallic nanoparticles were face centered cubic (fcc) in structure. FTIR spectra of the nanoparticles showed main absorptions at 3364.81 cm-1(-OH stretching vibrations), 2925.49 cm-1 (asymmetric stretching of C-H groups), 1650.59 cm-1(stretching vibrations C=O (amide and aldehyde), 1384.67 cm-1 (C-N stretching vibrations of amines) and 1067.62 cm-1(COH stretching of secondary alcohols) indicating the nanoparticles are capped with the bioactive compounds present in the plant extract.